Sang culture: social comparisons of generation Z Youths in Chinaon Social Media - Yang Weiqi,; Normaliza Abd Rahim,; Loh, Benjamin Yew Hoong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sang Culture emerged among Chinese youth, showcasing digital expressions that encompass written words, audio clips, visuals and videos that portray feelings of despair and decadence. This phenomenon offers insight into the lived experiences and attitudes of Chinese Generation Z, commonly known as Gen Z. Rising from the challenges of the 2020 pandemic, the guarded and pessimistic mindset of this generation towards existential fears and uncertainties is distinctive, particularly on social media, where the youth find comfort in a sense of belonging, channelling their expressions through ironic wit and light-hearted jokes, resulting in not only personal healing but also shared amusement. While it is being embraced as a means of self-expression and discourse on societal norms, Sang Culture has faced criticism from conservative Chinese society for its perceived disruptive nature. In stark contrast to traditional beliefs and philosophies, Sang Culture and its cynicism are often considered a societal stain. Nevertheless, as China's youth continue to navigate their place in a rapidly changing society, Sang Culture remains a powerful force, reflecting the aspirations and frustrations of a generation seeking to carve out its own path. This study examined Gen Z through the Sang Culture on social media platforms and analysed social comparisons that emerge from the Sang Culture expressions online. The analysis deployed Festinger’s Social Comparison Theory and findings of this study underline how the creation of user-generated content concerning the Sang Culture compare their perceptions, beliefs, attitudes, and behaviours with those dictated or implied by societal realities.